Pengaruh Program Kartu Prakerja Pasca Pandemi Covid 19 terhadap Pendapatan dan Manfaat Jangka Panjang Bagi Rumah Tangga di Kota Payakumbuh - Eka Novia Herdiamy; Rahma Elsa Fitriani; Mardhiyya Azhari; Wahyu Nusantara Illahi.S; Al - Amin; Febrina Adita Putri (Journal on Education, 2023)
The Pre-Employment Card Program is an implementation of Article 27 (2) of the 1945 Constitution of the Republic of Indonesia which reads: "Every citizen has the right to work and a decent living. The purpose of this study is the Effect of the Post-Covid 19 Pandemic Pre-Employment Card Program on Income and Long-Term Benefits for Housewives. The research method used is quantitative with multiple regression analysis using SPSS version 18. This research was conducted on Household who received the pre-employment card program. The total population was 100 people. The results of this study are that Pre-Employment Card has a significant influence on income and benefits. So that H1 states the alleged influence of Pre-Employment Karu on income and benefits, so H2 states the alleged influence of post-pandemic 19 on income and benefits received.